Review of the Empirical Evidence for Superluminal Particles and the 3 + 3 Model of the Neutrino Masses - Robert Ehrlich (Advances in Astronomy)
A review is given of hypothetical faster-than-light tachyons and the development of the author’s 3+3 model of the neutrino mass states, which includes one tachyonic mass state doublet. Published empirical evidence for the model is summarized, including an interpretation of the mysterious Mont Blanc neutrino burst from SN 1987A as being due to tachyonic neutrinos having m2=-0.38eV2. This possibility requires an 8 MeV antineutrino line from SN 1987A, which a new dark matter model has been found to support. Furthermore, this dark matter model is supported by several datasets: γ-rays from the galactic center, and the Kamiokande-II neutrino data on the day of SN 1987A. The KATRIN experiment should serve as the unambiguous test of the 3+3 model and its tachyonic mass state.